Pengembangan E-Modul Etnomatematika Batik Berbasis PjBL untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Cahyadi, Firman; M. Zainuddin; Arifin, Slamet (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This research aims to develop a valid, practical, and effective batik ethnomathematics e-module based on Project Based Learning (PjBL) to improve critical thinking skills of elementary school students. This research was conducted using the 4D RnD model design. In the research stages, product validation was carried out by media experts and material experts. The research product was tested with 19 fourth-grade students consisting of 9 boys and 10 girls. Research data was collected using interviews, questionnaires, and tests. Interviews were used to investigate initial conditions and needs, student and teacher questionnaires were used to assess the practicality of the e-module, and tests were conducted to assess students' critical thinking skills. Data analysis was carried out using descriptive statistics and t-tests. Based on the research results, it was found that (1) the batik ethnomathematics e-module was declared valid and feasible to be implemented, (2) the batik ethnomathematics e-module was declared practical, and (3) the batik ethnomathematics e-module was declared effective and proven to be able to improve students' critical thinking skills.